Studi Cross Sectional Terhadap Faktor Risiko Hipertensi pada Remaja - Rezekiyah, Sholeha; Wahyuni, Evi; Karwiti, Witi; Nasrazuhdy, Nasrazuhdy; Lestari, Wuni Sri (Journal of Telenursing (JOTING), 2023)
This study aims to look at the risk factors for hypertension in adolescents. The method is observational analytical research using a cross-sectional design involving 63 respondents. The research results showed that the 63 teenagers willing to be respondents in this study were aged 14 - 18 years, with the majority being female. The research results showed that the gender variable was not related to the incidence of hypertension in adolescents (p = 0.245), as well as the sleep duration variable (p = 0.477), the BMI variable (p = 0.000), light exposure (p = 0.000) and total cholesterol levels. (p = 0.007) shows a relationship with the incidence of hypertension in adolescents. The research conclusion is that the incidence of hypertension in adolescents is related to BMI, light exposure, and total cholesterol levels. Keywords: Risk Factors, Hypertension, Adolescents